Association of Germline Mutations in the Fumarate Hydratase Gene and Uterine Fibroids in Women With Hereditary Leiomyomatosis and Renal Cell Cancer - Stewart, Laveta (2008)
OBJECTIVE: To investigate the risk of uterine fibroids and other reproductive risk factors in women with hereditary leiomyomatosis and renal cell cancer (HLRCC). DESIGN: Case-control study. SETTING: National Institutes of Health, Rockville, Maryland. PATIENTS: A family-based case-control study was conducted between July 1, 2004, and June 30, 2006, including 105 women from families with HLRCC ascertained throughout North America. A telephone interview was conducted with all participants using a standardized questionnaire that elicited information about their menstrual, pregnancy, uterine fibroid, and hormonal contraceptive use history. Diagnosis of uterine fibroids was confirmed by pathologic diagnosis and by medical record review. DNA was extracted from blood samples and was screened for germline mutations in the fumarate hydratase (FH) gene. MAIN OUTCOME MEASURES: FH germline mutation status, presence of uterine fibroids, age at diagnosis, and symptoms and treatment of uterine fibroids. RESULTS: Of 105 women, 77 reported a history of uterine fibroids. Regardless of uterine fibroid status, 75 of 105 women had a germline mutation in FH (FH(mut) positive). The risk of uterine fibroids in FH(mut)-positive women was statistically significantly increased compared with that in FH(mut)-negative women (odds ratio [OR], 7.6; 95% confidence interval [CI], 2.9–20.0), as it was among women clinically affected with HLRCC compared with those clinically unaffected with HLRCC (8.6; 3.1–24.0). The median age at uterine fibroid diagnosis for FH(mut)-positive women (28 years) was significantly younger than that for FH(mut)-negative women (38 years) (P=.03). Women with a germline mutation in FH or clinically affected with HLRCC reported younger age at menarche (P < .004) compared with FH(mut)-negative women (P =.02) or women who were clinically unaffected with HLRCC. Women with HLRCC were more likely to have had treatment for uterine fibroids (OR, 4.6; 95% CI, 1.4–15.8), including hysterectomy (P=.02) at an earlier age compared with women who were clinically unaffected with HLRCC. CONCLUSIONS: This study provides the first evidence (to our knowledge) that women with germline mutations in FH and with clinical HLRCC have an increased risk of developing uterine fibroids. These women also have a younger age at uterine fibroid diagnosis and are more likely to have treatment for uterine fibroids at a younger age than women without HLRCC in their families.